The effectiveness of rocket stoves in reducing household waste in Danau Baru Village - Annisa Anggraini; Hasna Nadila Arahman; Khoirun Nisa; Fitria Fasari; Khayla Vita Rosa; Imam Warmansyah (Privietlab, 2026)
This study examines the issue of waste management in Danau Baru Village, which does not yet have a waste disposal site, resulting in the community still disposing of waste into the river, and tests the rocket stove as a contextually appropriate technological solution. Using a Participatory Action Research (PAR) approach, the study was conducted through participatory diagnosis, planning, implementation, observation-evaluation, and reflection with the active involvement of the community. Data were collected through participatory observation, semi-structured interviews, documentation, and field notes, then analyzed qualitatively. The results show that participatory rocket stoves are relevant and have gained initial social acceptance, but their sustainability is highly dependent on changes in sorting behavior, consistency of use, and institutional strengthening and assistance. Therefore, this technology is best positioned as a transitional solution towards a sustainable community-based waste management system.